Toward effective forecast of professionally important sensorimotor cognitive abilities of young soccer players - Ljach, V.; Witkowski, Z.; Guinik, B.; Samovarov, A.; Nash, D. (Perceptual and Motor Skills, 2012)
Development of skill in young soccer players relies on progressive improvement in different professionally important sensorimotor cognitive abilities. Development of seven leading abilities was based on the results of 23 tests provided for experimental and control groups. 600 elite young soccer players of both sexes, ages 11 to 19 years, were assessed over a period of 4 years. Experimental groups were given different exercises to aid development of selected abilities. At the end of the monitoring period, the experimental groups demonstrated a significant improvement in contrast to the control groups, and the greatest improvements in different test performances were observed in the 11- to 13-year-olds. The test-retest data show the testing process to be reliable. The study provides standard pedagogical models and data for trainers, coaches, and researchers working with young soccer players. Future research on talent identification and selection should adopt a multidimensional approach.